2017
DOI: 10.1002/er.3809
|View full text |Cite
|
Sign up to set email alerts
|

Simulation analysis of cooling methods of an on-board organic Rankine cycle exhaust heat recovery system

Abstract: Energy saving and emission reduction of engines were taken seriously, especially for vehicular diesel engines.\ud Exhaust heat recovery based on organic Rankine cycle (ORC) system has been considered as an effective\ud approach for improving engine fuel economy. This article presents the investigation of water or air cooling\ud method for an ORC exhaust heat recovery system on a heavy duty truck through simulations. The models of\ud the truck engine and the ORC system were developed in GT-suite, and the integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…To improve the economy of vehicles and to protect the environment, the waste gas energy should be reused. Turbo compounding [1,2], direct heat recovery [3] and turbocharging [4,5] are the common ways to do so. The turbocharger is essentially a kind of air pumps, which is widely used in vehicle internal combustion engines to increase the intake pressure.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the economy of vehicles and to protect the environment, the waste gas energy should be reused. Turbo compounding [1,2], direct heat recovery [3] and turbocharging [4,5] are the common ways to do so. The turbocharger is essentially a kind of air pumps, which is widely used in vehicle internal combustion engines to increase the intake pressure.…”
Section: Introductionmentioning
confidence: 99%
“…As for waste heat recovery techniques, organic Rankine cycle (ORC) is considered as a promising technology due to its small size, low emissions, and great power adaptability . Zhao et al found that for engines combined with ORC system, water cooling method was conducive to waste heat recovery, leading to a higher power output and thermal efficiency. They also concluded that ambient temperature influenced system performance directly.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of the use of renewable energy and waste heat, supercritical ORCs are attracting more and more attention as a promising energy‐to‐power transition technology . In recent years, the focus of ORC research has gradually shifted from thermodynamic studies for working fluids and system optimization to experimental and components studies, which has raised more pressing requirements for fluid‐to‐fluid scaling methods. So many kinds of working fluids are used for various heat sources in ORC systems that it is impossible to conduct experiments with every fluid.…”
Section: Introductionmentioning
confidence: 99%